On the Issue of Evolution of Taliban Movement in Afghanistan - Al. Al. Knyazev (Сравнительная политика, 2024)
The article examines the changes taking place in the Taliban movement, in comparison with various episodes from Afghan history including their dependence on Pakistan, issues of fragmentation and consolidation in the movement itself. A comparative analysis of the Taliban’s commitment to various interpretations of Islam and Sharia in the 1990s and after their second rise to power in 2021 is carried out. The author analyzes the dynamics of changes in the Taliban’s policy in the field of interethnic relations, as well as the problems of their inclusion in the life of Afghan society. The relationship between the Taliban movement and international terrorist groups is also examined. The author draws attention to the stereotypical views regarding the Taliban, which are widespread in the world and prevent an objective assessment of this phenomenon.